KETOKOHAN KEPALA YAYASAN SDIT AL MUSTOPA Dr.H.M. SUBKI ABDULKADIR DALAM PRIVILAGE PENDIDIKAN SEKOLAH - Fadilah, Ahmad Arif (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
This study discusses the Characteristics of the Head of the SDIT AL Mustopa in the Privilege of School Education. This study aims to determine the leadership of the Head of the Foundation in the privilege of Education. Foundations have an important role in advancing education, especially in madrasas, most of which are private madrasas. This study focuses on the role and function of foundations in improving the quality of education in madrasas. This study aims to determine the role of the SDIT AL Mustopa Foundation in managing madrasas, especially in achieving the National Education Standards. In addition, this study also wants to know how the function of the foundation, especially in fostering in madrasas managed by the foundation. This study uses a qualitative-descriptive approach. The results showed that the role of the SDIT AL Mustopa i foundation in providing education in Kindergarten, elementary school, junior school, high school SDIT AL Mustopa was quite good in providing education at the SDIT AL Mustopa Foundation in accordance with the National Education Standards, the Foundation had more of a role in financial management, resource management. Humans (HR), and infrastructure. The function of fostering the foundation has been carried out, especially in the development of human resources (HR), coaching in increasing faith and piety to Allah swt. And coaching in mastering science and technology in accordance with the times. In addition to coaching in the world of education, the SDIT AL Mustopa Foundation also helps in the fields of health, economy, social and religion.